2022
DOI: 10.3389/fpls.2022.994058
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E synthesis and response in plants

Abstract: Vitamin E, also known as tocochromanol, is a lipid-soluble antioxidant that can only be produced by photosynthetic organisms in nature. Vitamin E is not only essential in human diets, but also required for plant environment adaptions. To synthesize vitamin E, specific prenyl groups needs to be incorporated with homogentisate as the first step of reaction. After decades of studies, an almost complete roadmap has been revealed for tocochromanol biosynthesis pathway. However, chlorophyll-derived prenyl precursors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 95 publications
0
6
0
2
Order By: Relevance
“…For example, we identified elements from two important hormone signaling pathways, gibberellin and abscisic acid ABA, in chromosomes 1 and 8: PPR proteins have been associated to the response to drought, salt and cold stresses in Arabidopsis by negatively regulating ABA signaling pathways, while DELLA proteins are negative regulators of gibberellin signaling pathways. Furthermore, we identified a gene encoding an enzyme from the tocopherol (vitamin E) biosynthetic process, which is in turn an important antioxidant that protects thylakoid membrane lipids from photooxidation and helps plants cope with high light and heat stress ( Niu et al., 2022 ). In chromosome 9 we identified a GDSL-type esterease/lipase protein, associated to drought tolerance in soybean ( Su et al., 2020 ), and in chromosome 7 we found a gene model encoding a nuclear transcription factor Y subunit B-8.…”
Section: Resultsmentioning
confidence: 99%
“…For example, we identified elements from two important hormone signaling pathways, gibberellin and abscisic acid ABA, in chromosomes 1 and 8: PPR proteins have been associated to the response to drought, salt and cold stresses in Arabidopsis by negatively regulating ABA signaling pathways, while DELLA proteins are negative regulators of gibberellin signaling pathways. Furthermore, we identified a gene encoding an enzyme from the tocopherol (vitamin E) biosynthetic process, which is in turn an important antioxidant that protects thylakoid membrane lipids from photooxidation and helps plants cope with high light and heat stress ( Niu et al., 2022 ). In chromosome 9 we identified a GDSL-type esterease/lipase protein, associated to drought tolerance in soybean ( Su et al., 2020 ), and in chromosome 7 we found a gene model encoding a nuclear transcription factor Y subunit B-8.…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin E is synthesized only by plants and algae, making it essential for all animals to obtain it from their diet [13]. Once ingested, this fat-soluble vitamin is stored in the liver and released to other organs as needed [14].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon could be explained that (a) metabolic flux has a preference towards chlorophyll biosynthesis compared with tocopherol accumulation and (b) carotenoids protected chlorophylls against photodestruction. After all, accumulated studies have suggested that phytol supplied to tocopherol biosynthesis is primarily derived from chlorophyll degradation ( Niu et al, 2022 ). In addition, it was well documented that the photoinhibition effect of lights on stem elongation and carotenoid accumulation were coordinated in mung bean sprouts ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%